Green governance in maritime infrastructure development East Java as the new gateway of a sustainable Nusantara - Endika, Yepri (Privietlab, 2025)
This study explores the implementation of green governance in East Java’s maritime infrastructure development as the principal gateway to sustainable Nusantara. Positioned strategically as a national logistics and socio-economic hub connecting Java and Indonesia’s new capital (IKN), East Java possesses strong institutional, geographic, and community capacities to lead the green maritime transition. This research highlights how environmentally responsible port management, the efficiency and transparency of the Sea Toll program, and collaborative governance among the government, regional enterprises, MSMEs, and coastal communities contribute to sustainable development. Despite regulatory fragmentation, limited funding, and low environmental literacy, grassroots innovation and civic participation have emerged as transformative social capital. This study emphasizes the need to strengthen public policy alignment, expand fiscal incentives for sustainable ports, and enhance community-based environmental education as key strategies to accelerate an inclusive and socially responsive maritime governance model that supports IKN connectivity and regional welfare.